Desenvolvimento de sistemas de liberação contendo metotrexato como uma nova abordagem terapêutica da artrite reumatoide - Agostini, Sandra Barbosa Neder (2020)
The goal of this work was to develop metrotrexate (MTX)-loaded delivery systems in order to improve the rheumatoid arthritis therapy. Three kinds of MTX delivery systems was developed: polyelectrolyte complexes (PECs), thermosensitive hydrogel and association between PECs and hydrogel. The PECs were composed by polimeric chitosan or oligochitosan and hypromellose phtalate (HPMCp). Ionic strength adjustement was used in order to optimize the chitosan PECs size and polydispersity. The optimized chitosan PECs (QS 200) exhibited 345±79 nm particle size (measured by dynamic light scattering technique), 0.285±0.067 polydispersity index (PdI), +19±2 mV zeta potential at 5.5 pH and 29.5±24.2% drug entrapment efficiency (EE). Because of its narrow size distribution, QS200 was used to select cryoprotectants, among them mannose was the most efficient to mantain the PECs physicochemical properties. Among the oligochitosan PECs, OQ-7 presented 471±116 nm particle size, 0.308±0.127 PdI, +26±2 mV at 5.9 pH and 74.3±5.8% EE. The PECs formation and the MTX loading were proved by infrared spectroscopy and thermal analysis. QS200 and OQ-7 were also characterized by atomic force microscopy. The hydrogels were based on poloxamer 407 and poloxamer 188 mixture and were loaded with MTX, QS200 or OQ-7. At room temperature, the hydrogels were fluid and showed suitable seringueability. Between 36° and 37° C, the hydrogels became thick and stopped flowing. The sharp elastic modulus increase at body temperature was observed by oscilatory rheometry technique. In vitro drug release assay was conducted and showed that the MTX release was slower from the PECs (OQ-7 or QS200) incorporated in hydrogel. The performance of OQ-7 and hydrogel loaded with OQ-7 or MTX, once administrated by intra-articular route, was evaluated in rats with rheumatoid arthrites induced. Although its vehicle had shown irritant effect, because of its anti-inflammatory effects on nociception, IL-1β plasmatic level and knee joint histology, OQ-7 was noted as the most promising treatment. Thus, PECs have great potential for treating rheumatoid arthritis.